Expeditions to Knowledge (2010)
The article presents the experiences of the groups participating in Expeditions to Knowledge, second stage of EAFIT Children's University, in 2010. Topics such as history, music, interculturality, seismic engineering, economy, art in the city, marine geology, the fourth dimension and robotics were addressed.